Inovasi Pelayanan Pemerintahan Dalam Mewujudkan Good Governance Di Negara Bagian Terengganu Malaysia (BERDAYA : Jurnal Pengabdian Kepada Masyarakat, 2024)
Public services are an important pillar in realizing good governance. One of the efforts to realize good governance is to innovate public services. The state of Terengganu realizes good governance through service innovation. Good governance is the process of decision-making and policy implementation based on the principles of transparency, accountability, participation, effectiveness, efficiency and the rule of law. The innovation made by the Terengganu government in realizing good governance is the implementation of e-government called Terengganu Government Digital Service and the Terengganu Smart City Program. Through these service innovations, it can increase the efficiency of public services and public trust in the government. One of the important things in realizing good governance is community participation in the government process.